PENGARUH PENGGUNAAN METODE PICTORIAL RIDDLE TERHADAP HASIL BELAJAR DASAR LISTRIK DAN ELEKTRONIKA SISWA SMK NEGERI 1 LEMBAH MELINTANG PASAMAN BARAT - Mustafa Mustafa; Legiman Slamet; Nelda Azhar (Universitas Negeri Padang, 2018)
The problem in this study is the low average learning outcomes of learners on Electrical and Electronics Elementary subjects is under the Minimum Criteria of completeness (KKM) that has been established SMK Negeri 1 Lembah Melintang is 75. This study aims to determine the influence of the use of Pictorial Riddlemethod with Cooperative learning on student learning outcomes in Electrical and Electronics Elementary subjects in class X TAV SMK Negeri 1 Lembah Melintang. This type of research is experimental research with Postest Only Control Design. The research sample is XTAV2 class as experiment class using Pictorial Riddle Method and XTAV1 class as control class using Cooperative learning. Technique of collecting data from final test in experiment class and control class, then analyzed for homogeneity test, normality test and hypothesis test. From the experimental class research results obtained an average value of 83.22, while the control class get an average value of 75.83. Result of hypothesis calculation at significant level α = 0,05 got tcount> ttable that is 3,2> 1,674, because big tcount of ttable, null hypothesis (H0) rejected and alternative hypothesis (H1) accepted. Can be concluded mean at the real level, this research shows that, there is influence of positive student learning result between the use of Pictorial Riddle Method with Cooperative learning on Electrical and Electronics Elementary subjects in class X TAV SMK Negeri 1 Lembah Melintang Pasaman Barat. Then the Pictorial Riddle Method is better compared to direct learning.Keywords: Riddle Pictorial Method, Cooperative Learning, Learning Outcomes, Experiments, Controls.